2013
DOI: 10.1021/bi401494f
|View full text |Cite
|
Sign up to set email alerts
|

Formal Reduction Potential of 3,5-Difluorotyrosine in a Structured Protein: Insight into Multistep Radical Transfer

Abstract: The reversible Y-O•/Y-OH redox properties of the α3Y model protein enable access to the electrochemical and thermodynamic properties of 3,5-difluorotyrosine. The unnatural amino acid has been incorporated at position 32, the dedicated radical site in α3Y, by in vivo nonsense codon suppression. Incorporation of 3,5-difluorotyrosine gives rise to very minor structural changes in the protein scaffold at pH below the apparent pK (8.0 ± 0.1) of the unnatural residue. Square-wave voltammetry on α3(3,5)F2Y provides a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(73 citation statements)
references
References 57 publications
5
68
0
Order By: Relevance
“…Rapid freeze-quench (RFQ)-EPR spectroscopy of the reaction between F 2 Y 356 -β2, Y 731 F-α2, CDP, and ATP at pH 8.2 and 25 °C revealed F 2 Y 356 • at 3 ± 1% of the total radical concentration. This observation provided a Δ E °′(F 2 Y 356 •–Y 122 •) of 70 ± 5 mV, which along with our recent measurement of the reduction potential of F 2 Y in a protein environment 23,25 gives an estimate of Δ E °′(Y 356 •–Y 122 •) of ∼100 mV at pH 7.6. The results of the site specifically incorporated unnatural amino acids described herein together with our previous studies allow us to propose a thermodynamic landscape for the RT pathway in the E. coli class Ia RNR that is ∼200 meV uphill between Y 122 and C 439 .…”
Section: Introductionsupporting
confidence: 66%
“…Rapid freeze-quench (RFQ)-EPR spectroscopy of the reaction between F 2 Y 356 -β2, Y 731 F-α2, CDP, and ATP at pH 8.2 and 25 °C revealed F 2 Y 356 • at 3 ± 1% of the total radical concentration. This observation provided a Δ E °′(F 2 Y 356 •–Y 122 •) of 70 ± 5 mV, which along with our recent measurement of the reduction potential of F 2 Y in a protein environment 23,25 gives an estimate of Δ E °′(Y 356 •–Y 122 •) of ∼100 mV at pH 7.6. The results of the site specifically incorporated unnatural amino acids described herein together with our previous studies allow us to propose a thermodynamic landscape for the RT pathway in the E. coli class Ia RNR that is ∼200 meV uphill between Y 122 and C 439 .…”
Section: Introductionsupporting
confidence: 66%
“…30 Voltammetry characterization of the 2e − α 3 NH 2 Y redox system differs relative to the previously studied 1e − α 3 Y, 16, 30 2-mercaptophenol-α 3 C, 51 the α 3 F n Ys, 15, 16 and α 3 W 52 proteins. The combination of a less oxidizing potential range and a 2e − current, yielded protein film cyclic voltammograms of excellent quality (e.g.…”
Section: Discussionmentioning
confidence: 63%
“…37 The α 3 scaffold increases the radical t 1/2 dramatically (×10 4 for Y 32 • and W 32 • relative to Y• (aq) and W• (aq) 42, 52 and has allowed reversible voltammograms and E °’ values to be obtained on Y 32 , W 32 and a number of tyrosine analogs. 15, 16, 30, 51, 52 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…44,45 SWV was used to obtain formal E °′(radical/amino acid) protein potentials for α 3 Y, 33 2MP-α 3 C, 28 and α 3 (3,5)F 2 Y. 30 The α 3 X potentials are pH dependent and measurements performed at low pH are more difficult due to the higher potentials and more pronounced background currents involved. 33 SWV on α 3 (2,3,5)F 3 Y, α 3 (2,3)F 2 Y, and α 3 (2,3,6)F 3 Y was predicted to be challenging since measurements had to be done ~ pH 5.5 (≥ 1.7 pH units below the p K app ’s of the α 3 F n Y proteins) and test studies on α 3 (2,3,5)F 3 Y placed E °′ well above +1 V. Voltammetry data from an on-going parallel project involving an α 3 (NH 2 )Y variant (Lee, Nocera, Stubbe and Tommos) suggested that a protein film approach, where the protein is introduced to the surface of the working electrode outside the electrochemical cell, improves the Faradaic response of the α 3 X system.…”
Section: Resultsmentioning
confidence: 99%